Discriminant analysis of cluster B personality disorders based on interpersonal problem - Reza Asadi; Parviz Sabahi (روانشناسی و روانپزشکی شناخت, 2023)
Introduction: Personality disorders have a wide impact on people's personal and social life. Aim: The present study aimed to determine the degree of differentiation of cluster B personality disorders based on interpersonal problems. Method: The design of the current research was descriptive and of a comparative causal type. The statistical population included all people with cluster B personality disorder in the 5 districts of Arak city in 2022. Based on the number of research groups and variables, 120 people were selected from among those who referred to the psychology and addiction treatment centers of Arak city using the available method and responded to the Clinical Multiaxial Scales of Milon version 4 (2015) and Interpersonal Problems (1996), people were also evaluated by Structured Clinical Interview for Personality Disorders (2016). To analyze the data, the discriminant analysis method was used in SPSS software version 26. Results: The results indicate a significant difference between the components of sociable (P=0.001), assertive (P=0.001), aggressive (P=0.001), caring (P=0.001), dependent (P=0.008), supportive (P=0.001), and involved (P=0.001) in the studied groups, but did not show a significant difference between the studied groups (P=0.14). In total, based on the evaluated components, 68.3% of the participants were correctly placed in their groups. Conclusion: Considering that in the present study, most of the dimensions of interpersonal problems were significant in people with cluster B personality disorders, as a result, this variable can be used to differentiate the personality disorders of this cluster and also the intervention plan.